Judgement and decision making in clinical and return-to-sports decision making: A narrative review - Yung, K. K.; Ardern, C. L.; Serpiello, F. R.; Robertson, S. (Sports Medicine, 2024)
Making return-to-sport decisions can be complex and multi-faceted, as it requires an evaluation of an individual`s physical, psychological, and social well-being. Specifically, the timing of progression, regression, or return to sport can be difficult to determine due to the multitude of information that needs to be considered by clinicians. With the advent of new sports technology, the increasing volume of data poses a challenge to clinicians in effectively processing and utilising it to enhance the quality of their decisions. To gain a deeper understanding of the mechanisms underlying human decision making and associated biases, this narrative review provides a brief overview of different decision-making models that are relevant to sports rehabilitation settings. Accordingly, decisions can be made intuitively, analytically, and/or with heuristics. This narrative review demonstrates how the decision-making models can be applied in the context of return-to-sport decisions and shed light on strategies that may help clinicians improve decision quality.